Recognizing, Measuring, and Interpreting The Potential/Enacted Power Distinction In Organizational Research - Provan, Keith G. (Academy of Management Review, 1980)
Although theoretical conceptualizations of power suggest that the concept has both potential and enacted components, attempts to measure and interpret power using this distinction have been rare in empirically based studies of organizations. In this paper, I explain the theoretical distinction between potential and enacted power and then discuss the measurement and interpretation of each, especially with respect to macrolevel organizational research. I review and categorize the major approaches used by organizational researchers in measuring organizational power, focusing on the strengths and weaknesses of each measure in making the potential/enacted distinction, and concluding that a multidimensional approach to measuring organizational power is best.